Konsumsi makanan dan status gizi anak balita di Kelurahan Pasar Lahewa Kecamatan Lahewa Kabupaten Nias Utara - Telaumbanua, Marnilam; Wahab, Abdul; Siagian, Masryna; Simanjuntak, Mafe Robbi; Pakpahan, Eka Lolita Eliyanti; Simanullang, Andry; Gultom, Dameria (Jurnal Kesmas Prima Indonesia, 2024)
Food consumption is one of the direct causes of nutritional status. The Ministry of National Development Planning in 2019 reported that almost half of the population or 45.7 percent of the population is very poor in energy allowances and 36.1 percent of the population is low in protein allowances. Meanwhile, the North Sumatra Provincial Health Office in 2019 presented the results of monitoring nutritional status which showed the three districts with the highest stunted of children under five, namely Gunung Sitoli, West Nias, and Samosir. The districts with the most underweight of children under five are West Nias, Central Tapanuli, and North Nias. The purpose of the study was to determine the relationship between food consumption and the nutritional status of children under five at Pasar Lahewa Village, Lahewa Sub-District, in North Nias District, which was selected purposively. This type of research is descriptive analytic, cross sectional design. The food consumption data of sixty children under five were collected using the 24-Hour Food Recall Method for three non-consecutive days, anthropometric nutritional status with Body Weight Index according to Height or Body Length. The results showed that the largest contribution of energy and protein samples came from rice, powdered milk, chicken, fish, eggs, tofu, tempeh, potatoes, noodles, and biscuits. Most of the samples were categorized as well consumption and normal nutritional status. The Chi-Square test produces a p-value of 0.003 (p<α (0.05) which means Ho is rejected so that it can be stated that there is a relationship between food consumption and the nutritional status of children under five at Pasar Lahewa Village, Lahewa District in North Nias District. The results are expected can be used by the leadership and staff of the Lahewa District Health Center to plan nutrition improvement programs. Similar research needs to be carried out in other villages within the working area of the Lahewa District Health Center, to obtain and enrich data in planning program to improve food consumption and nutritional status of children under five.